Teori Corporate Governance: Keterbatasan, Kritik dan Alternatif - Novianto, Wawan; Firdaus, Firdaus (Universitas Batanghari Jambi, 2024)
Corporate governance is a crucial element in supporting the competitiveness and sustainability of companies in a dynamic business environment. This article discusses three main theories underpinning corporate governance: agency theory, stakeholder theory, and stewardship theory. These theories offer different perspectives on the relationships between managers and stakeholders and their impact on effective governance. This research employs a qualitative approach with an interpretivist paradigm to understand the social constructions and subjective meanings of corporate governance practices in Indonesia. The findings reveal that while good governance generally enhances company performance, the effectiveness of various governance elements differs. Cultural factors and ownership structures also play a significant role in determining the form and success of corporate governance. These insights provide new perspectives for formulating more flexible and contextual governance strategies.